SHOPVIS: VISUALISASI INTERAKTIF PERSEBARAN TOKO DARING DI INDONESIA MENGGUNAKAN CROWDSOURCED DATA - Handayani, Ruktin; Rasyidi, Mohammad Arif (SISFO, 2019)
The current statistics on electronic-commerce distribution in Indonesia mostly only reveal the number and value of transactions, but not the distribution, both in terms of the quantity of online stores and the types of goods sold. This study aims to develop a visualization of the distribution of online stores in Indonesia. The data used in this study is crowdsourced data taken from one of online marketplaces in Indonesia. The data is analyzed and processed to produce statistics on the distribution of online stores by region and type of goods. These statistics are displayed in map visualization for ease of use. This visualization can be utilized by the government or stakeholders to monitor the development of online stores in each region and make strategic decisions. The visualization can be used further to obtain statistics and the distribution of the types of goods sold online, comparing them to ordinary trade and typical products from each region. Underdeveloped regions can then be motivated to develop their electronic commerce to their full potential. This research is also expected to be used as a reference for even distribution of electronic commerce in Indonesia.